Lymphoepithelioma-like carcinoma with carcinosarcoma of the endometrium: a case report and literature review - Xu, Jialing; Huang, Bin; Zhu, Yanhua; Shi, Jianping; Zhou, Qiang (Frontiers in Immunology, 2025)
This report describes a 56-year-old female diagnosed with lymphoepithelioma-like carcinoma with carcinosarcoma of the endometrium (LELCCSE). She experienced vaginal bleeding and lower abdominal discomfort without any obvious cause following six years of menopause. She sought treatment at our hospital in Hangzhou, China. An ultrasound examination revealed a hypoechoic mass within the uterus. Subsequently, a biopsy confirmed it as lymphoepithelioma-like carcinoma (LELC) with carcinosarcoma.The patient underwent a total hysterectomy, bilateral salpingo-oophorectomy, and associated lymphadenectomy. The postoperative pathology suggested LELC complicated with carcinosarcoma and an IIC grade by the 2023 FIGO staging system. She received adjuvant chemotherapy and radiotherapy without any molecular testing due to her financial constraints. A gene which encodes the catalytic subunit of DNA polymerase epsilon(POLE) mutation was found by the retrospective molecular testing; however, no recurrence or metastasis occurred after 12 follow-up months.